The other side of the corona: nanoparticles inhibit the protease taspase1 in a size-dependent manner. Issue 37 (14th July 2020) - van den Boom, Johannes; Hensel, Astrid; Trusch, Franziska; Matena, Anja; Siemer, Svenja; Guel, Désirée; Docter, Dominic; Höing, Alexander; Bayer, Peter; Stauber, Roland H.; Knauer, Shirley K.
Abstract : Adsorption of biomolecules to nanoparticles leads to corona formation, affecting not only the nanomaterial's identity, but also protein function: Taspase1 protease activity is inhibited by silica particles in a size-dependent, noncompetitive manner. Abstract : When nanoparticles enter a physiological environment, they rapidly adsorb biomolecules, in particular cellular proteins. This biological coating, the so-called nanoparticle protein corona, undoubtedly affects the biological identity and potential cytotoxicity of the nanomaterial. To elucidate a possible impact on the adsorbed biomolecules, we focused on an important group of players in cellular homeostasis, namely proteolytic enzymes. We could demonstrate that amorphous silica nanoparticles are not only able to bind to the oncologically relevant threonine protease Taspase1 as revealed by microscale thermophoresis and fluorescence anisotropy measurements, but moreover inhibit its proteolytic activity in a non-competitive manner. As revealed by temperature-dependent unfolding and CD spectroscopy, binding did not alter the stability of Taspase1 or its secondary structure. Noteworthy, inhibition of protein function seems not a general feature of nanoparticles, as several control enzymes were not affected in their proteolytic activity. Our data suggests that nanoparticles bind Taspase1 as an αβ-dimer in a single layer without conformational change, resulting in noncompetitive inhibition that is either allostery-like or occludes the active site. Nanoparticle-based inhibition of Taspase1 could be also achieved in cell lysates and in live cells as shown by the use of a protease-specific cellular cleavage biosensor. Collectively, we could demonstrate that nanoparticles could not only bind but also selectively inhibit cellular enzymes, which might explain observed cytotoxicity but might serve as a starting point for the development of nanoparticle-based inhibitors as therapeutics.